PECULIARITIES OF CONDUCTING COMPREHENSIVE FORENSIC PSYCHOLOGIC AND PSYCHIATRIC EXPERT EVALUATIONS AMONG WOMEN WITHIN THE FRAMEWORK OF CRIMINAL PROCESSES - Revenok, Oleksander; Radzevilova, Oleksandra; Oliinyk, Oksana (PSYCHOLOGICAL JOURNAL, 2018)
This Article is dedicated to researching the issue of female criminality, and namely, to conducting forensic expert evaluations of ability of women who committed violent crimes to realize the significance or their actions and (or) manage such actions. We present the results of analysis of 169 conclusions of forensic psychiatric expert evaluations and comprehensive forensic psychologic and psychiatric expert evaluations within criminal proceedings involving the mentioned category of persons (for the period of 2010-2016). This analysis has allowed to highlight typical mistakes in assigning forensic expert evaluations in various categories of crimes, including the crimes where the offender is dependent on the object of a criminal act. This article cites a structured medical criterion for incompetence or limited competence of mentioned females at the time of delict (based on the researched subjects). The structure of the medical criterion for incompetence includes mental disorders that annihilate the ability of a person to stay aware of her actions and manage such actions at the time of a criminal act due to psychotic symptoms and/or severe disorder of the behavior-regulating intellectual component. Meanwhile, the structure of the medical criterion for limited incompetence included cases where females were not capable of fully realizing their actions (or lack of thereof) and manage such actions due to explicit behavioral disorders. Such cases envisage that possible intellectual disorders were offset specifically by explicit disturbance of emotions and volition. It was discovered that despite females having mental disorders of varying origin and degree of severity (expert evaluations conducted in 2010-2016), only a small percentage of these women were considered “incompetent/of limited competency” based on the medical criterion. Taking this into account as well as severity of a delict, research of the psychological criterion of competence highlights, first and foremost, psychological peculiarities of female criminals and analysis of a crime situation. Based on the above-mentioned, we have defined the necessity of different approaches and opinions among psychologists (as forensic experts and psychodiagnostics experts) during expert evaluations depending on the object of a criminal act. In addition, in the course of a psychological expert evaluation of ability to be aware of one’s actions and manage such actions during a crime explicitly directed against life and health of a person, we shall necessitate a body of grounded evidence of presence or absence of not only a physiological affective state, but also other emotional states (frustrations, tension) at the time of a crime, while noting their possible influence on awareness and actions of a person at the moment of delict.